Leopoldo Chiappo, ten years after his death - León, Ramón (2020)
This communication reviews the conceptual contribution of Leopoldo Chiappo (1924-2010) to Peruvian psychology ten years after his death. His contributions in the field of neuropsychologyand his studies around the Divine Comedy, by Dante Alghieri, and the significance of this work for psychological knowledge are discussed, as well as his important teaching work of trainingpsychologists.